Trade Liberalization Index and Economic Growth in Developing Countries: Does Stage of Development Matter? (Economic Journal of Nepal, 2021)
This paper analyses the widely used Sachs and Warner (1995) index of trade liberalization for 193 countries extending the period up to 2009 identifying 134 countries as open, 23 countries as closed, and 36 countries with ambiguous status, and then investigates the impacts of trade liberalization on economic growth using a dynamic growth model for a disaggregated levels of income. For this purpose, this study uses the biggest panel data set in this literature covering the period of 1985-2009. The results show that the impact of trade liberalization on economic growth differs based on the income levels of the developing countries. As indicated by the estimated results, the lower-middle-income countries, on average, benefit up to 3.45 percent points more compared to other developing countries from the trade liberalization. This finding makes a strong case for a clear departure from the ‘Washington Consensus’ approach and claims that trade liberalization with the same priority to all developing countries does not ensure economic growth. Also,  the findings strongly suggest considering the stage of economic development of the developing countries while recommending their trade policy reforms.